Implementación de un proceso administrativo para la hostería Cotopaxi tour en la parroquia Tanicuchi, cantón Latacunga, provincia de Cotopaxi - Arcentales Marcalla, Guadalupe Patricia (2015)
The lack of an administrative process in the private companies is evident due to some people, who run them have an empirical knowledge in their administration, this has encouraged the development of this job, where the investigator seeks to implant an administrative process to Cotopaxi Tour Inn, which will have a systematically developing, through the planning, organizing, directing and controlling of all the activities and company services. Planning is a process, where we have to take decision for getting the desired future, taking into a count that all activities and actions which were done by the company must be planned to ensure that the services will be of quality. The organization consists in the elaboration of organigrams, the departmentalization of the jobs activities which will help to coordinate, the available resources between the members of the company….